Stock Assessment of Panulirus Homarus in Southeastern Madagascar Using a Rectified Virtual Population Analysis - Raberinary Daniel; Dizano Arison Valerio; Assanaly Valencia; Mahatante Tsimanaoraty Paubert; Mara Edouard Remanevy (Ite Ngabdi, 2026)
Effective stock assessment is fundamental for the sustainable management of data-limited fisheries. This study assessed the stock status of the spiny lobster (Panulirus homarus) in southeastern Madagascar using a Rectified Virtual Population Analysis (VPA), a pseudo-cohort approach suitable for fisheries with limited age-structured data. Biological measurements of 5,624 individuals collected from artisanal fishery landings between 2018 and 2020 were combined with historical catch and fishing effort data from 2014 to 2020. Carapace length measurements were converted into annual age classes to reconstruct population abundance, estimate age-specific fishing mortality, and evaluate stock status through a yield-per-recruit (YPR) model. The reconstructed population consisted of ten age classes, with catches dominated by individuals aged two to three years. Fishing mortality was highest among lobsters aged two to five years, while population abundance declined progressively with increasing age. The YPR analysis indicated that the current exploitation level exceeds the biological reference point corresponding to the Maximum Sustainable Yield (MSY), demonstrating that the stock is already overexploited. These findings highlight the need to reduce fishing effort, strengthen compliance with minimum legal-size regulations and seasonal closures, promote selective fishing gears, and implement continuous biological monitoring. The study demonstrates that Rectified VPA provides a practical and reliable framework for assessing data-limited lobster fisheries and supports evidence-based management for the sustainable exploitation of P. homarus in southeastern Madagascar.